Vitamin D and female fertility - Lerchbaum, Elisabeth; Rabe, Thomas (Current opinion in obstetrics and gynecology, 2014)
Purpose of review - Apart from the well known effects of vitamin D on maintaining calcium homeostasis and promoting bone mineralization, there is some evidence suggesting that vitamin D also modulates human reproductive processes. We will review the most interesting and relevant studies on vitamin D and female fertility published over the past year. - Recent findings - In the past year, several observational studies reported a better in-vitro fertilization outcome in women with sufficient vitamin D levels (≥30 ng/ml), which was mainly attributed to vitamin D effects on the endometrium. One randomized controlled trial found an increased endometrial thickness in women with polycystic ovary syndrome (PCOS) receiving vitamin D during intrauterine insemination cycles. Further, vitamin D supplementation had a beneficial effect on serum lipids in PCOS women. Vitamin D treatment improved endometriosis in a rat model and increased vitamin D intake was related to a decreased risk of incident endometriosis. Vitamin D was also favorably associated with primary dysmenorrhea, uterine leiomyoma, and ovarian reserve in late reproductive aged women. - Summary - In women undergoing in-vitro fertilization, a sufficient vitamin D level (≥30 ng/ml) should be obtained. Vitamin D supplementation might improve metabolic parameters in women with PCOS. A high vitamin D intake might be protective against endometriosis.